Plasma parathyroid hormone is independently related to nocturnal blood pressure in hypertensive patients: the Styrian Hypertension Study - Verheyen, Nicolas; März, Winfried (The journal of clinical hypertension, 2016)
High parathyroid hormone (PTH) has been linked with high blood pressure (BP), but the relationship with 24-hour ambulatory blood pressure monitoring is largely unknown. The authors therefore analyzed cross-sectional data of 292 hypertensive patients participating in the Styrian Hypertension Study (mean age, 61±11 years; 53% women). Median plasma PTH (interquartile range) determined after an overnight fast was 49 pg/mL (39-61), mean daytime BP was 131/80±12/9 mm Hg, and mean nocturnal BP was 115/67±14/9 mm Hg. In multivariate regression analyses adjusted for BP and PTH-modifying parameters, PTH was significantly related to nocturnal systolic and diastolic BP (adjusted β-coefficient 0.140 [P=.03] and 0.175 [P<.01], respectively). PTH was not correlated with daytime BP readings. These data suggest a direct interrelationship between PTH and nocturnal BP regulation. Whether lowering high PTH concentrations reduces the burden of high nocturnal BP remains to be shown in future studies.